The impact of idealism, Volume 1, Philosophy and natural sciences the legacy of post-Kantian German thought - Ameriks, Karl 1947-; Boyle, Nicholas 1946-; Disley, Liz (Cambridge University Press, 2013)
The first study of its kind, The Impact of Idealism assesses the impact of classical German philosophy on science, religion and culture. This volume explores German Idealism's impact on philosophy and scientific thought. Fourteen essays, by leading authorities in their respective fields, each focus on the legacy of a particular idea that emerged around 1800, when the underlying concepts of modern philosophy were being formed, challenged and criticised, leaving a legacy that extends to all physical areas and all topics in the philosophical world. From British Idealism to phenomenology, existentialism, pragmatism and French postmodernism, the story of German Idealism's impact on philosophy is here interwoven with man's scientific journey of self-discovery in the nineteenth and early twentieth centuries – from Darwin to Nietzsche to Freud and beyond. Spanning the analytical and Continental divide, this first volume examines Idealism's impact on contemporary philosophical discussions